Gender-smart agriculture: What, Why and How - Huyer, Sophia; Chanana, Nitya (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This InfoNote expands on the AICCRA gender case study on women-targeted strategies to develop gender-responsive CSA and explains the broad steps and indicators to implement, monitor and measure gender-responsive CSA. It highlights a Gender-Smart Agriculture (GSA) approach that considers women’s priorities and access to technology, resources, and information to support climate resilience through equality and agency. GSA targets gender equality and empowerment of women and men, taking CCAFS research beyond diagnostic and equity approaches towards research to inform, catalyze and target CSA solutions for women and youth, increase their control over productive assets and resources (e.g., climate information, climate finance), and increase their leadership and decision-making (e.g., in local and national climate adaptation) . This expanded approach also includes a focus on social inclusion, involving gender, socioeconomic status, ethnicity, disability, and age (youth and seniors).